Pengelolaan Surat Menyurat Pada Bidang Peerdagangan Luar Negeri Dinas Perindustrian Dan Perdagangan Kota Medan - Arsiah Dwi Cintana; Anggita Damayanti (ABDI DAYA: Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2024)
trade sector of the Medan City Industry and Trade Service. This research was carried out by identifying the process of managing incoming and outgoing email as well as the limitations caused by a management system that still uses manual methods. The research results show that manual methods such as the use of agendas are still used in managing incoming and outgoing communications in this sector. The obstacles faced in managing these letters are limited physical space to store and manage incoming and outgoing emails, difficulty finding emails due to the lack of automatic search capabilities, security including the risk of emails being lost or damaged due to the lack of built-in systems. In this situation, it is necessary to use an email management application that can simplify the process of managing emails electronically. This application can increase the efficiency, accuracy and security of email management and minimize the risk of email loss or damage. Additionally, mail-order applications allow easy and flexible access to mail from various locations. Finally, management of correspondence in the field of foreign trade at the Medan City Industry and Trade Service needs to be improved through the introduction of mail applications to increase the efficiency and effectiveness of the management process. The implementation of this application is expected to overcome manual obstacles.